The effects of particle size and volume fraction of Al2O3 on electronic thermal conductivity of ?-Al2O3 particulate reinforced aluminum composites (Al/Al2O3MMC) - Özdemir, N; Yakuphanoğlu, Fahrettin (Springer London Ltd, 2006)
The effects of particle size and volume fraction of Al2O3 on the thermal conductivity properties of alpha-Al2O3 particulate reinforced aluminum composites (Al/Al2O3MMC) are investigated herein. It is found that the thermal conductivity of composites is higher with an Al2O3 particle size of 15 mu m than with a particle size of 30 mu m. The increase in the thermal conductivity could be due to the greater stability of thermal conductive paths with smaller Al2O3 particles.
Keywords: composites; electrical properties; thermal conductivity